أثر الإختلاف بين النظام المحاسبي المالي والنظام الجبائي الجزائري على الوعاء الضريبي - بنكوس المختار (جامعة البليدة2-كلية العلوم الإقتصادية والعلوم التجارية وعلوم التسيير, 2023)
الملخص باللغة العربية: هدفت هذه الدراسة إلى تبيين وتحليل العلاقة بين المحاسبة والجباية في الجزائر، وذلك في ظل فك الارتباط بينهما منذ تطبيق النظام المحاسبي المالي مطلع سنة ،2010حيث تم الوقوف على أهم معالم الإختلاف بين القواعد المحاسبية وفقا للــ SCFوقواعد النظام الجبائي الجزائري في تقييم عناصر القوائم المالية والاعتراف بالأعباء والنواتج، مع توضيح أثر هذا الاختلاف على عملية تحديد الوعاء الضريبي لدى المؤسسات الاقتصادية الجزائرية، وتوصلت الدراسة إلى جملة من النتائج والاستنتاجات أهمها أن القواعد الجبائية لا تتوافق مع القواعد المحاسبية بسبب إختلاف الأهداف بينهما، إضافة لمبالغة المحاسبة في تسجيل الأعباء وتبني مفاهيم جديدة قائمة على تفضيل الجوهر الاقتصادي على الشكل القانوني، كما بينت الدراسة أن الأثر الناجم عن الاختلاف بين النظامين يؤدي إلى ظهور نوعين من الفروقات، إحداهما دائمة تؤثر على الدورة التي حدثت فيها فقط دون أن يمتد تأثيرها إلى الدورات اللاحقة، وأخرى مؤقتة تنشأ منها ضرائب مؤجلة يمتد تأثيرها إلى الدورات اللاحقة إما بالسداد أو الاسترداد. وخلصت الدراسة إلى جملة من الاقتراحات والتوصيات، أهمها اقتراح تكييف قواعد النظام الجبائي الجزائري مع متطلبات النظام المحاسبي المالي من خلال تغليب الواقع الاقتصادي على الشكل القانوني والتوسع في اعتماد محاسبة الاستحقاق على حساب محاسبة الصندوق، إضافة لتحيين النظام المحاسبي المالي والنظام الجبائي الجزائري وفقا للمستجدات المحاسبية على الساحة الدولية بصفة عامة والمعيار المحاسبي الدولي IAS 12بصفة خاصة وذلك بغرض تقديم قوائم مالية تتسم بالجودة والمصداقية من جهة ولتحديد وعاء ضريبي عادل وشفاف من جهة أخرى. الكلمات المفتاحية: نظام محاسبي مالي، نظام جبائي، وعاء ضريبي، فروقات دائمة، فروقات مؤقتة، ضرائب مؤجلةAbstract in English: This study aimed to clarify and analyze the relationship between accounting and taxation in Algeria, in light of the disengagement between them since the application of the financial accounting system in early 2010, where the most important features of the difference between the accounting rules according to the SCF and the rules of the Algerian taxation system were identified in evaluating the elements of the financial statements. And the recognition of the burdens and outputs, with an explanation of the impact of this difference on the process of determining the tax base of the Algerian economic institutions. Preferring the economic essence over the legal form, and the study showed that the effect resulting from the difference between the two systems leads to the emergence of two types of differences, one of which is permanent affecting the cycle in which it occurred only without its effect extending to subsequent sessions, and another temporary one arising from deferred taxes whose effect extends to subsequent cycles, either by payment or refund. The study concluded with a number of suggestions and recommendations, the most important of which is the proposal to adapt the rules of the Algerian tax system with the requirements of the financial accounting system by prevailing the economic reality on the legal form and expanding the adoption of accountability accounting at the expense of the fund accountability, in addition to updating the financial accounting system and the Algerian tax system in accordance with accounting developments on The international arena in general and the international accounting standard IAS 12 in particular, in order to provide financial and credibility lists on the one hand and to determine a fair and transparent tax base on the other hand. Keywords: financial accounting system, tax system, tax base, permanent differences, temporary differences, deferred taxes.
دراسة ميدانية
Keywords: نظام محاسبي مالي; نظام جبائي; الضريبة; دائمة; مؤقتة; ضرائب مؤجلة